Corn Cost-Return Budget in Western Kansas - Dumler, Troy J.; Thompson, Curtis R. (My University, 2006)
This publication provides estimated cost and returns for forward farm planning for corn in western Kansas.
MF2150_2006_10
Keywords: MF2150; Crops; Economics; MF